Surfactant Administration through Laryngeal Mask Airway: A Randomized Controlled Study in Rabbits - Bernardo, Cristian A.; Mariani, Gonzalo L.; Virasoro, María de los Ángeles; Burgos, Sebastián; Labanca, María J.; Otero, Pablo (American Journal of Perinatology, 2018)
Background Minimally invasive techniques for surfactant administration for infants with respiratory distress syndrome (RDS) of moderate severity have been proposed. The laryngeal mask airway (LMA) helps in securing the airway without the need of laryngoscopy, but still requires the use of positive pressure ventilation (PPV) to flush surfactant into the lungs.Objective This article compares the effectiveness of two techniques for LMA surfactant administration, instillation into the LMA lumen followed by PPV versus direct laryngeal instillation through a preinserted feeding tube inside the LMA during spontaneous respirations.Study Design This is a randomized controlled trial (RCT) of 18 rabbits with acquired respiratory distress after lung lavage. After surfactant was given, the rabbits remained on continuous positive airway pressure (CPAP). Gas exchange parameters were assessed at baseline and at 30 minutes and lung parenchyma pathology features were analyzed.Results Time required for surfactant administration, oxygenation improvement, and histopathologic findings did not differ between groups. The new technique decreased the need of PPV (p < 0.05).Conclusion In this animal model, surfactant administration through a preinserted feeding tube within the LMA lumen is safe and effective while providing the benefits of a minimally invasive approach. This technique reduces the need of PPV and may prevent its potential risks.
Keywords: respiratory distress syndrome; less invasive surfactant administration; laryngeal mask airway; gentle approach